Rh(i) and Ru(ii) phosphaamidine and phosphaguanidine (1, 3-P, N) complexes and their activity for CO2 hydrogenation. Issue 33 (31st July 2019) - Kandel, Ramjee; Schatte, Gabriele; Jessop, Philip G.
Abstract : Phosphaamidine and phosphaguanidine complexes Rh2 Cl2 L2 (μ-CO), RuCl2 L2, [RhL′(COD)]BF4, RuCl2 L′(DMSO)2 and RuCl2 L′′(DMSO)2 (L = Ph2 PC(Ph)NPh, L′ = [ i Pr2 PC(Ph)N i Pr, L′′ = Me2 NC(PPh2 )N i Pr) are shown to be precatalysts for CO2 hydrogenation. Abstract : Phosphaamidine metal complexes Rh2 Cl2 [Ph2 PC(Ph)NPh]2 μ-CO (1 ), RuCl2 [Ph2 PC(Ph)N(Ph)]2 (2 ), [Rh{ i Pr2 PC(Ph)N i Pr}(COD)]BF4 (3 ), and RuCl2 [ i Pr2 PC(Ph)N i Pr](DMSO)2 (4 ) are prepared by combining phosphaamidines Ph2 P-C(Ph)NPh and i Pr2 P-C(Ph)N i Pr (1, 3-P, N) with their corresponding metal ions. Complexes1 and2 are stable in air while3 and4 are stable under inert conditions. For further comparison of structure and stability, a Ru(ii ) phosphaguanidine complex, RuCl2 [Me2 NC(PPh2 )N i Pr](DMSO)2 (6 ) was prepared. Complex6 is stable in air and in the presence of water. The structures of the phosphaamidine and phosphaguanidine complexes, determined using single crystal X-ray diffraction, revealed P, N bidentate coordination. While all five complexes have some activity as precatalysts, complex6 was the most active.